The Toll for Trafficking: Toll-Like Receptor 7 Delivery to the Endosome - Petes, Carlene; Odoardi, Natalya; Gee, Katrina (Frontiers in Immunology, 2017)
Toll-like receptor (TLR)-7 is an endosomal innate immune sensor capable of detecting single-stranded ribonucleic acid (ssRNA). TLR7-mediated induction of type I interferon (IFN) and other inflammatory cytokine production is important in anti-viral immune responses. Furthermore, altered TLR7 expression levels are implicated in various autoimmune disorders, indicating a key role for this receptor in modulating inflammation. This review is focused on the regulation of TLR7 expression and localization compared to that of the other endosomal TLRs: TLR3, 8, and 9. Endosomal TLR localization is a tightly controlled and intricate process with some shared components among various TLRs. However, TLR-specific mechanisms must also be in place in order to regulate the induction of pathogen- and cell-specific responses. It is known that TLR7 is shuttled from the endoplasmic reticulum (ER) to the endosome via vesicles from the Golgi. Several chaperone proteins are required for this process, most notably UNC93B1, recently identified to also be involved in the localization of the other endosomal TLRs. Acidification of the endosome and proteolytic cleavage of TLR7 are essential for TLR7 signaling in response to ligand binding. Cleavage of TLR7 has been demonstrated to be accomplished by furin peptidases in addition to cathepsins and asparagine endopeptidases (AEP). Moreover, triggering receptor expressed on myeloid cells like 4 (TREML4), a protein associated with antigen presentation and apoptosis in immune cells, has been implicated in the amplification of TLR7 signaling. Understanding these and other molecular mechanisms controlling TLR7 expression and trafficking will give insight into the specific control of TLR7 activity compared to the other endosomal TLRs.